Low impact building - Woolley, Tom (Wiley-Blackwell, 2013)
(What are) renewable and non-renewable materials -- Case studies, the 12 projects in the renewable house programme -- The Renewable House Programme: a strange procurement! -- Analysis of issues arising from the case studies -- Attitudes to renewable materials, energy issues and the policy context -- Building physics, natural materials and policy issues -- Other solutions for low energy housing -- The future of renewable materials?; Includes bibliographical references and index; "Low Impact Building: Housing using Renewable Materials is about changing the way we build houses to reduce their 'carbon' footprint and to minimise environmental damage. One of the ways this can be done is by reducing the energy and environmental impact of the materials and resources used to construct buildings by choosing alternative products and systems. In particular, we need to recognise the potential for using natural and renewable construction materials as a way to reduce both carbon emissions but also build in a more benign and healthy way. This book is an account of some attempts to introduce this into mainstream house construction and the problems and obstacles that need to be overcome to gain wider acceptance of genuinely environmental construction methods